Purification of the Vertebrate Nuclear Pore Complex by Biochemical Criteria - Miller, Brian R. (Traffic, 2000)
The nuclear pore is a large and complex biological machine, mediating all signal-directed transport between the nucleus and the cytoplasm. The vertebrate pore has a mass of ~120 million daltons or 30 times the size of a ribosome. The large size of the pore, coupled to its tight integration in the nuclear lamina, has hampered the isolation of pore complexes from vertebrate sources. We have now developed a strategy for the purification of nuclear pores from in vitro assembled annulate lamellae (AL), a cytoplasmic mimic of the nuclear envelope that lacks a lamina, nuclear matrix, and chromatin-associated proteins. We find that purified pore complexes from annulate lamellae contain every nuclear pore protein tested. In addition, immunoblotting reveals the presence of soluble transport receptors and factors known to play important roles in the transport of macromolecules through the pore. While transport factors such as Ran and NTF2 show only transient interaction with the pores, a number of soluble transport receptors, including importin β, show a tight association with the purified pores. In summary, we report that we have purified the vertebrate pore by biochemical criteria; silver staining reveals ~40–50 distinct protein bands.